2019
DOI: 10.3390/app9010150
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Open Source Clinical Software on GitHub for Improving Software Reuse in Smart Healthcare

Abstract: The plethora of open source clinical software offers great reuse opportunities for developers to build clinical tools at lower cost and at a faster pace. However, the lack of research on open source clinical software poses a challenge for software reuse in clinical software development. This paper aims to help clinical developers better understand open source clinical software by conducting a thorough investigation of open source clinical software hosted on GitHub. We first developed a data pipeline that autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Push for “Code Reuse”. Both open access publishing and open source software repositories present important models which can support the growth, replication, consistency, and inclusivity across clinical research [ 108 , 109 ]. We found that 44% of the studies identified in this review were open access, which is well above the 28% average [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Push for “Code Reuse”. Both open access publishing and open source software repositories present important models which can support the growth, replication, consistency, and inclusivity across clinical research [ 108 , 109 ]. We found that 44% of the studies identified in this review were open access, which is well above the 28% average [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we found that no studies provided any open software to accompany their articles. Open-source software repositories (i.e., GitHub) can support cost-effective replication, advancement, and growth of software for clinical research [ 107 ]. Although limited, such examples are already present in the field of wearable technology [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some papers review the state of the open source implementations for a given topic. For example, Shen et al surveyed open source implementations of clinical software available in GitHub [67]. Both Dozmorov and Russel et al [60,22] use GitHub to survey open source implementations of bioinformatics software.…”
Section: Related Workmentioning
confidence: 99%